Unlocking the potential of peatlands and paludiculture to achieve Germany’s climate targets: obstacles and major fields of action - Wichmann, Sabine; Nordt, Anke (Frontiers in Climate, 2024)
Greenhouse gas emissions from drained peatlands must be substantially reduced to meet climate mitigation targets. In Germany, annual peatland emissions of 53 Mt CO2e account for more than 7% of total national GHG emissions. Peatland drainage and reclamation is traditionally considered as a symbol of progress and technical achievement, where agriculture has been the major driver. In Germany, an area of 1.3 million ha of drained peatlands used for agriculture ought to be rewetted by 2050 to meet the 1.5°C target of the Paris Agreement. Paludiculture allows a productive use of wet peatlands instead of abandonment following rewetting. This approach might therefore pave the way for voluntary large-scale peatland rewetting. However, implementation remains scarce. The long history and large extent of peatland drainage has shaped the political and legal framework as well as perceptions and attitudes, thus impeding rewetting and climate-friendly peatland use. This policy and practice review investigates the political, legal, economic and social aspects that hinder the implementation in Germany and derives approaches to overcome multifold restrictions. Finally, three major fields of action are identified: 1) To increase and accelerate rewetting, a consistent peatland mainstreaming approach is needed that overcomes structural barriers and adapts the policy and legal framework, e.g. the Common Agricultural Policy, planning law, water law and nature conservation law. 2) To motivate for a rapid transition, a system of immediate, comprehensive and attractive positive incentives is needed. This should be accompanied by early announcement and gradual introduction of negative incentives to set a clear course and provide planning certainty for farmers and landowners. 3) A just transition depends on empowering local communities to develop and pursue perspectives tailored to their peatland region. Future research of peatlands as social-ecological systems can help to identify region-specific drivers for sustainable peatland management.